2017
DOI: 10.1007/s10803-017-3364-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mental Health in Chinese Parents of Children with Autism Spectrum Disorder (ASD)

Abstract: The aim of this study was to explore the influence of parental intolerance of Uncertainty (IU), sensory sensitivity (SS) and Broader Autism Phenotype (BAP), as well as the severity of their children's autism symptoms and co-morbid symptoms, on the mental health of Chinese parents of children with autism spectrum disorder (ASD). One hundred and twenty-two parents (86.9% mothers; M = 35.64 years, SD = 4.21) of children with ASD took part. Regression and mediation analyses showed that children's internalizing dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…Only mothers participated in our study. As hypothesized, both greater intolerance of uncertainty and higher use of avoidant coping predicted anxiety and depression, which supports previous work in parents [Hastings et al, 2005; Su et al, 2017]. We also found that lower use of problem‐focused coping additionally contributed to depression but not anxiety.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only mothers participated in our study. As hypothesized, both greater intolerance of uncertainty and higher use of avoidant coping predicted anxiety and depression, which supports previous work in parents [Hastings et al, 2005; Su et al, 2017]. We also found that lower use of problem‐focused coping additionally contributed to depression but not anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…Intolerance of uncertainty has been shown to be a risk factor for generalized anxiety disorder [Dugas et al, 1997] and major depressive disorder [Miranda, Fontes, & Marroquin, 2008]. Higher levels of intolerance of uncertainty has been shown to predict increased negative affective symptoms including anxiety, depression, and stress in two separate samples of parents of children with ASD [Su, Cai, & Uljarevi c, 2017;Uljarevi c et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found that the "advantage" of DS continues to be present after controlling the effect of demographic, family, or social factors (e.g., Smith et al, 2014). Other factors could also be associated with parental stress and other aspects of parents' mental health, such as differences between the diagnostic processes for the two disorders (Rivard et al, 2014), and even aspects intrinsic to the family itself, such as the so-called broader autism phenotype (Su et al, 2018).…”
Section: Demographic and Social Factors Involved In Parental Stress Imentioning
confidence: 99%
“…Additionally, the small sample size of Su and colleagues' study [21] and Peters-Scheffer et al's study [38] may not have been adequate for the accurate prediction of cross-section study results concerning the association between behavior problems and high level of parenting stress. The small sample sizes may have also affected the findings and led to discrepancies.…”
Section: Behavior Problemsmentioning
confidence: 89%
“…However, there seemed to be contradictory evidence about the significance of the relationship between parenting stress and problem behaviors. For instance, the findings of a study by Su and colleagues [21] and Peters-Scheffer et al [38] revealed that the relationship between parenting stress and problem behaviors was not significant. These studies [21,38] only considered the viewpoints of the mothers and lacked involving the views of the fathers.…”
Section: Behavior Problemsmentioning
confidence: 99%